Relationships between self-efficacy and high-performance sport: A systematic review - Aizava, P. V. S.; dos Santos Oliveira, I. F.; de Oliveira, D. V.; Garcia, W. F.; Fiorese, L. (Paidéia (Ribeirão Preto), 2024)
Self-efficacy is defined as people`s beliefs in their own abilities to achieve something. This study aimed to systematically review the literature on psychological variables associated with self-efficacy in sport. Searches were conducted in six electronic databases: LILACS, PubMed, SciELO, SPORTDiscus, Web of Science, and Scopus, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Content analysis of 29 included articles allowed for the identification of three research groups: psychological variables (n = 31; 72.1%), performance variables (n = 7; 13.3%), and other variables (n = 5; 11, 6%). There was a predominance of cross-sectional quantitative studies (72.4%; n = 21). The most used instrument was the General Self-Efficacy Scale (GSE), with 13 (44.8%) articles. In seven (24.1%) articles, specific questions were developed for the study. It is concluded that self-efficacy is a widely studied variable, but there is a lack of specific instruments in the Brazilian context of high-performance sports.